1988
DOI: 10.1002/art.1780311210
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cyclobenzaprine and placebo in the management of fibrositis

Abstract: The efficacy of cyclobenzaprine (Flexeril), as compared with placebo, was tested in a 12‐week, double‐blind, controlled trial of 120 patients with fibrositis. Of the patients who received placebo, 52% dropped out due to lack of efficacy of the drug, compared with 16% of patients taking cyclobenzaprine. The dropout rate due to adverse reactions was similar in the 2 groups. Patients taking cyclobenzaprine experienced a significant decrease in the severity of pain and a significant increase in the quality of slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
5

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(62 citation statements)
references
References 12 publications
(3 reference statements)
0
57
0
5
Order By: Relevance
“…This high use of alternative medicine amongst FMS patients is not surprising considering the generally poor response to current treatment options and suggests that patients are actively seeking other modalities in order to improve symptoms (3,(7)(8)(9)(10)(11)(12)(13)(14). We did not explore the severity of symptoms or outcome of F M S in patients using alternative therapies and, thus, we are Additions to diet 16 (20) Subtractions from diet 20 (25) Dietary modifications unable to make any assessment of the impact of such treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This high use of alternative medicine amongst FMS patients is not surprising considering the generally poor response to current treatment options and suggests that patients are actively seeking other modalities in order to improve symptoms (3,(7)(8)(9)(10)(11)(12)(13)(14). We did not explore the severity of symptoms or outcome of F M S in patients using alternative therapies and, thus, we are Additions to diet 16 (20) Subtractions from diet 20 (25) Dietary modifications unable to make any assessment of the impact of such treatment.…”
Section: Discussionmentioning
confidence: 99%
“…69 Fibromyalgia is another condition in which efficacy of TCAs is reasonably well-established. 55,[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] Most studies have reported that TCAs were effective at doses lower than those needed for the treatment of depression. 80,83 The analgesic effect size (ES) (difference between 2 means [antidepressant analgesic effectplacebo analgesic effect] divided by the pooled estimate standard deviation) of TCAs ranged from 0.23 to 1.34 in fibromyalgia.…”
Section: (Continued)mentioning
confidence: 99%
“…In addition to amitriptyline 18 and duloxetine, 19 other antidepressants, such as fl uoxetine 20 and milnacipran, 21,22 and several other drugs, such as ciclobenzaprine, 23,24 gabapentin, 25 pregabalin, 26,27 and tramadol, 28,29 have been tested in controlled studies and have shown promising responses in relieving fi bromyalgia symptoms. Although all the above-cited drugs have been studied and have been part of these patients' pharmacological therapy, currently, duloxetine and pregabalin are the only drugs approved by the Food and Drug Administration (FDA) for treating fi bromyalgia.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%